2015
DOI: 10.1111/jrh.12113
|View full text |Cite
|
Sign up to set email alerts
|

Medical Education to Improve Rural Population Health: A Chain of Evidence From Alabama

Abstract: Within limitations of the study design, these findings support the proposition that the number of medical students produced in a county is related to the number of primary care physicians, which is related to life expectancy. Recommendations are to confirm the findings in other populations and inform public health policy concerning the utility of medical education to address population health by producing local medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This suggestion is in line with another study from Alabama that found counties with more students in medical school had more primary care physicians and longer life expectancy. 32 As counties involve more students in these pipelines, we could expect them also to seek ways to better attract these pipeline students into local practice. These efforts might be internal to the community, such as local scholarships, shadowing opportunities, social recognition, and civic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is in line with another study from Alabama that found counties with more students in medical school had more primary care physicians and longer life expectancy. 32 As counties involve more students in these pipelines, we could expect them also to seek ways to better attract these pipeline students into local practice. These efforts might be internal to the community, such as local scholarships, shadowing opportunities, social recognition, and civic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…This map analysis was affected by small numbers of RMS. Subsequent unpublished data on RMS practice location support the pattern of infrequent location in the Black Belt, and published ecological data from a different dataset show a disparity in primary care workforce in this region …”
Section: Discussionmentioning
confidence: 89%
“…Subsequent unpublished data on RMS practice location support the pattern of infrequent location in the Black Belt, and published ecological data from a different dataset show a disparity in primary care workforce in this region. 39 As effective as the RMSP is, it is not sufficient to supply physicians needed for Alabama's rural Black Belt. This population of largely poor southern blacks is not limited to Alabama and is not trivial-it is one of the "eight Americas," one that experiences decreased access to health care compared to other populations.…”
Section: Addressing Assumptionsmentioning
confidence: 99%
“…The scarcity of healthcare professionals and resources necessitates innovative care strategies, underscoring the critical role of advanced practice nurses (APNs). These nurses, with specialized skills in assessment, diagnosis, and disease management, are pivotal in improving healthcare outcomes in rural settings [4,5].…”
Section: Introductionmentioning
confidence: 99%